Hubungan Permainan Congklak Untuk Meningkatkan Kognitif Anak Usia 4-5 Tahun Dalam Pendekatan Neurosains - Apindi, Ripda Yudani; Junika, Fely; Tulharmi, Lathifah; Lestari, Dita (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine the relationship between playing congklak and improving fine motor skills in children aged 5–6 years from a neuroscience perspective. This study used a descriptive qualitative research method with a literature review approach, which examined various previous research findings related to the influence of traditional games on neuromotor development in early childhood. Based on the literature analysis, playing congklak has been shown to be effective in stimulating hand-eye coordination, movement precision, and concentration in children. From a neuroscience perspective, playing congklak activates brain areas such as the motor cortex, cerebellum, and frontal lobe, which play a role in planning, coordinating, and controlling movement. This process supports the formation of neuroplasticity, the strengthening of new neural pathways that influence the improvement of children's sensorimotor and cognitive abilities. The study results indicate that playing congklak is not only a traditional recreational medium but also an effective and enjoyable brain-based learning tool. Therefore, integrating traditional games into learning activities in early childhood education (PAUD) is highly recommended to stimulate fine motor development while preserving local cultural values ​​in the digital age.